Land tenure: coping with change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Land tenure is becoming less secure in rural areas in ACP States. Competition for access to land and its resources is rising, under pressure from a variety of factors: migration from less-endowed parts of the Sahel, the growing thrust towards the...